Emotion Dysregulation Moderates the Association Between Stress and Problematic Cannabis Use - Cavalli, Jessica M.; Cservenka, Anita (Frontiers in Psychiatry, 2021)
Background. Research suggests emotion dysregulation is a transdiagnostic risk factor for substance use and addiction and that stress may lead to problematic cannabis use. Thus, the current study examines how emotion dysregulation moderates the associations between stress (stressful life events and perceived stress) and problematic cannabis use. Methods. 852 adults reporting any lifetime cannabis use completed an anonymous online survey. Participants completed a brief demographic questionnaire and were asked to report their past 30-day use of cannabis, alcohol, nicotine, and illicit substances. Problematic cannabis use (via the Marijuana Problem Scale), emotion dysregulation (via the Difficulties in Emotion Regulation Scale), perceived stress (via the Perceived Stress Scale) and stressful life events (via the Holmes-Rahe Life Stress Inventory) were assessed. Hierarchical multiple linear regressions were conducted. Results. Findings indicate that when examining the moderating role of emotion dysregulation, more stressful life events and less perceived stress were associated with more severe problematic cannabis use, and these associations were stronger at higher levels of emotion dysregulation. Conclusions. These results demonstrate a strong step toward understanding how emotion dysregulation moderates the relationship between stress and problematic cannabis use; however, longitudinal studies are needed to determine directionality of effects. Overall, these results suggest the importance of examining emotion dysregulation as a moderator of both stressful life events and stress perception as they relate to problematic cannabis use.